Petrarca nella Corte: Un modello di comportamento del cortegiano-umanista - Puskás, István (Verbum – Analecta Neolatina, 2005)
During the 15th and 16th century, Petrarch played an important role in the various areas of cultural and everyday life. One of the sources of his influence was that he could answer any question concerning his art, though the interpretations differed according to the various readings. This is what happened in the case of his opinion about the regal court, too. I intend to introduce one episode of this long story of the relationship between the humanist and the regal court influenced by Petrarca. This episode contains the story of Ferrara in the 15th century and Pandolfo Collenuccio, the literator.